India’s self-sufficiency policies for pulses and their implications for Myanmar - Roy, Devesh; Ajmani, Manmeet Singh; Boss, Ruchira; Pradhan, Mamata; Laitha, Andrew (International Food Policy Research Institute, 2022)
Globally, India is the largest producer and consumer of pulses, but increasing demand due to population growth has made the country reliant on imports, including from Myanmar. In turn, Myanmar is highly dependent on exports to India. A proposed advance purchase agreement between India and Myanmar in 2016 failed, but revisiting the original proposed purchase agreement could be in the best interest of both countries, as Myanmar could secure a large market for pulses at stable prices and India could ensure its supply of pulses.